Methodical instructions for laboratory classes in the discipline "Informatics" - Strelchuk, R. M. (My University, 2021)
This is the lab course, wherein you will have the hands on experience. You have studied the support course material (MCS-011 Problem solving and programming). In this part, C programming under DOS, UNIX and WINDOWS environments are provided illustratively. A list of programming problems is also provided at the end of each session. Please go through the general guidelines and the program documentation guidelines carefully.
Keywords: methodical instructions; information technology; UNIX; programming